Model‐free output feedback discrete sliding mode control with disturbance compensation for precision motion systems. Issue 14 (19th August 2020) - Li, Min; Tan, Shuhua; Xiong, Jiaxi; Gan, Jinqiang; Zhang, Xinxin
Abstract : This study proposes a novel model‐free output feedback discrete sliding mode control (OFDSMC) with disturbance compensation to achieve high performance for precision motion systems encountering model uncertainties and disturbances. Traditional discrete sliding mode control design requires model and/or state information. In this study, OFDSMC with disturbance compensation is first developed by using a parametric input–output model such that no system states are needed. The essential four control terms of OFDSMC with disturbance compensation is revealed. Then a data‐driven control method is introduced into OFDSMC to eliminate the need for the parametric model. The proposed model‐free OFDSMC facilitates a rapid implementation without either a parameter model or a state observer, and achieves good robustness against model uncertainties and disturbances. Finally, three simulation cases are presented to illustrate the effectiveness and enhanced performance of the proposed approach.